EGG QUALITY DETERMINATION OF F1 AND F2 CHICKEN SELECTED CROSSBRED OF BROILER COBB 500 x PELUNG - Mahardhika, I Wayan Swarautama; Saragih, Hendry T.S.S.G.; Widiyanto, Slamet; Daryono, Budi Setiadi (Buletin Veteriner Udayana, 2022)
Egg quality can determine the fertility and reproductive efficiency of chickens. Selective breeding of Kambro chickens might have influenced the egg quality. This study aims to determine the influence of a selective breeding program on the egg quality of two Kambro chicken generations, F 1 Kambro (F 2 K)-crossbred and F 2 Kambro (F 2 K)-inbred. Inbreeding coefficient ( F ) and rate of inbreeding ( Fx ) of F 2 K chickens were calculated. The egg collection record was analyzed based on its productivity, phenotype, weight, index, and exterior egg quality parameters. Exterior egg quality parameters were analyzed with mathematical formulae. Egg productivity in Hen Day Production (HDP) of F 1 K and F 2 K chickens for 270-days, respectively, was 24% and 16.5%. The heterosis value of F 2 K chicken was -31.25% indicating an inbreeding depression in egg productivity. The egg phenotype of F 2 K was classified into light-brown, cream, brown, and white. The mean egg weight (EW) of F 1 K and F 2 K, respectively, was 53.34 ± 2.34-grams and 54.92 ± 9.25-grams, thus were classified as small eggs. The eggshape index of F 1 K and F 2 K, respectively, were dominated by sharp eggs and round eggs. Exterior egg quality parameters of F 1 K and F 2 K based on GMD could be used as a predictor variable, meanwhile Sp (r = 1, p<0.001) could not be used to describe the disposition of the regression curve. The Fx and F values of F 2 K, respectively, were 4.925% and 25% close to the tolerance level of inbred-line inbreeding depression. Inbreeding depression was correlated with productivity and egg characteristics depression between F 1 K and F 2 K. Parental selection in a selective breeding program must be based on several factors, including inbreeding depression, inbreeding coefficient, inbreeding rate, and egg quality. The implementation of genomic selection may provide a solution to minimalize the effect and fluctuations of Fx and F .